A SEARCH FOR AN EAST MILLENARY KNOWLEDGE WHICH IS BEING SPREAD INTO THE WEST- YOGA- A HEALTHY AND WELFARE PRACTICE (Fiep Bulletin - online, 2013)
As seen in the numerous interrogations about this millenary practice Yoga - here begins a search about this subject, relatively complex. The idea of building a work about “yoga” is due to the way traveled during a field research, linked to the Doctorate by one of the PPGCSa in UFRN. During the research, it was observed a lack in an effective practice that would benefit the quality of life of elders housed there. In this article, in particular, the study focuses on the history of yoga, in Brazil, reporting consequently the introduction of Hinduism, which comes from the East. Therefore, we are, only, beginning the long journey is this search for knowledge, using studies that will get deeper, since Yoga, as any other science, requires commitment and determination to the search of constant knowledge. Yoga has been recognized, nowadays, as an important element of cultural and religious integration between East and West. Although Yoga cannot be considered a religion, it is a practice which comes from the Hinduism, carrying in it many references to this Eastern religion. Some of these have been dismantled in the West, especially with the spread of exercises in gyms - where the focus becomes the physical and aesthetic benefits deriving from them. But if some elements are omitted, others are still present - as the mantras, the greetings and the names of postures that tribute Hindu gods - especially in specialized centers. It is important, weaving in the search, to distinguish which elements of the religion are being kept and what elements have been modified in the Brazilian context. And, besides, to draw a path traveled by this Eastern practice to reach its current level of broadcasting in our society.
Keywords: culture; yoga; exercises